The dynamics of inequality change in a highly dualistic economy: Honduras, 1991-2007 - Stephan Klasen; Thomas Otter; Carlos Villalobos (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2012)
We examine the drivers of inequality change in Honduras between 1991-2007, trying to understand why inequality increased in Honduras until 2005, while it was falling in most other Latin American countries. Using annual household surveys, we document first rising inequality between 1991-2005, which is followed by falling inequality thereafter. Using an inequality decomposition technique, we show that the rising inequality between 1991 and 2005 was, for the most part, driven by the dispersion of labour incomes in rural areas. We also show that the extraordinary labour earnings disequalization is mainly the result of a widening wage gap between the tradable and non-tradable sectors and occupations, combined with highly segmented labor markets and poor overall educational progress. The underlying determinants of the divergence between tradable and non-tradable sectors were highly overvalued currencies and poor commodity process for Honduras' agricultural exports. Between 2005 and 2007, however, the inequality reduction was a result of equalizing trends in labour and non-labour incomes. The commodity boom promoting the tradable sector and remittances (in this order) played a significant role here, with government transfers playing a small supporting role. Since the decline in inequality is largely driven by international factors, we cannot be sure whether the decline in inequality will continue.
Keywords: C15; D31; I21; J23; J31; R23; J31; J61; 330; Inequality; Decomposition; Education; Wages; Honduras; Migration; Soziale Ungleichheit; Einkommensverteilung; Dekompositionsverfahren; Lohnstruktur; Ländlicher Raum; Nicht-handelbares Gut; Handelbares Gut; Honduras